2014
DOI: 10.1103/physrevlett.113.210403
|View full text |Cite
|
Sign up to set email alerts
|

Strong Monogamies of No-Signaling Violations for Bipartite Correlation Bell Inequalities

Abstract: The phenomenon of monogamy of Bell inequality violations is interesting both from the fundamental perspective as well as in cryptographic applications such as the extraction of randomness and secret bits. In this article, we derive new and stronger monogamy relations for violations of Bell inequalities in general no-signaling theories. These relations are applicable to the class of binary output correlation inequalities known as XOR games, and to a restricted set of unique games. In many instances of interest,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…While the no-signaling trade-off relation is general, it is an open question whether it is tight, i.e., whether there exists a Bell expression for which a network with n i=2 mi + 1 parties is needed before such a monogamy relation manifests itself. For instance, it has been found that for general two-party correlation inequalities, monogamy relations hold in networks with far fewer number of parties [39].…”
Section: A Different Quantum Box Which Achieves the Same Values Is Gimentioning
confidence: 99%
“…While the no-signaling trade-off relation is general, it is an open question whether it is tight, i.e., whether there exists a Bell expression for which a network with n i=2 mi + 1 parties is needed before such a monogamy relation manifests itself. For instance, it has been found that for general two-party correlation inequalities, monogamy relations hold in networks with far fewer number of parties [39].…”
Section: A Different Quantum Box Which Achieves the Same Values Is Gimentioning
confidence: 99%
“…This inequality cannot be violated, as quantum correlations are monogamous with respect to the chained Bell inequality [37,41]. Loosely speaking, if party B violates I chain with A, it cannot violate it simultaneously with C. For some types of monogamy relations, this result holds for various generalizations of the CHSH inequality to more measurements, outcomes and parties [42].…”
Section: B a Quasi Translationally Invariant Bell Inequalitymentioning
confidence: 99%
“…While this appears counterintuitive at first sight, we explain that this arises due to an incompatibility between the optimal classical strategies for the sub-expressions into which the commutation graph of the whole Bell expression is decomposed. In [10], it was shown that in the paradigmatic example of correlation inequalities for binary outcomes, the pa-…”
Section: Propositionmentioning
confidence: 99%
“…(00, 00, 00) (00, 00, 00) (00, 00, 00) (00, 00, 00) (00, 00, 01) (00, 00, 01) (00, 00, 01) (00, 00, 01) (00, 00, 10) (00, 10, 10) (00, 00, 10) (00, 11, 10) (00, 01, 00) (00, 01, 00) (01, 00, 01) (01, 01, 01) (01, 00, 00) (01, 01, 00) (00, 01, 01) (00, 01, 01) (01, 00, 11) (01, 11, 11) (01, 00, 11) (01, 10, 11) (01, 00, 10) (01, 10, 10) (10, 01, 01) (10, 00, 01) (10, 01, 00) (10, 00, 00) (01, 00, 11) (01, 10, 11) (10, 01, 11) (10, 10, 11) (10, 01, 11) (10, 11, 11) (01, 01, 10) (01, 11, 10) (11, 01, 00) (11, 01, 00) (11, 01, 01) (11, 01, 01) (01, 01, 11) (01, 11, 11) (11, 01, 10) (11, 11, 10) (11, 01, 10) (11,10,10) Conclusions. In this paper, we have presented a unified view on monogamy relations for Bell and noncontextuality inequalities derived from the physical principles of no-signaling and no-disturbance.…”
Section: A1b1c1 A1b2c1 A2b1c1 A2b2c1 A3b1c1 A3b2c1mentioning
confidence: 99%